Is Modern Monetary Theory a Real Solution for All US Economic Problems? - E. A. Chernysheva (Vestnik MGIMO-Universiteta)
Book review: Kelton S. 2020. The Deficit Myth. Sydney: McPhersons Printing Group. 325 p. ISBN 978-1-529-35253-5.